Information overload : a system for better managing everyday data - Pijpers, Guus, 1960- (Hoboken, N.J. : Wiley, 2010)
World-class guidance on using information to achieve better performance. Examining the characteristics of information and the latest findings in cognitive science, this book shows how the mind works, how it can be used to think optimally about your business, and how to improve business performance with better information management practices.: Provides the process and tools necessary to identify this information and how to remember it, and how to better use the people around you to obtain the best information; Reveals how to handle all of the hundreds of pieces of information received daily; P.
Information Overload: A System for Better Managing Everyday Data; CONTENTS; PREFACE; ACKNOWLEDGEMENTS; PART I: THE PRINCIPLES; CHAPTER 1: INFORMATION ON INFORMATION; CHAPTER 2: A LOT OF INFORMATION; CHAPTER 3: BRAIN MATTERS; CHAPTER 4: WE PEOPLE; PART II: IN PRACTICE; CHAPTER 5: INFORMATION PROFILE; CHAPTER 6: MIND YOUR BRAIN; CHAPTER 7: BRAIN AT WORK; CHAPTER 8: THE INFORMATION BRAIN; CHAPTER 9: INFORMATION AT WORK; CHAPTER 10: CLEVER COMMUNICATION; CHAPTER 11: PEOPLE AT WORK; REFERENCES; INDEX.
Includes bibliographical references (pages 185-190) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Knowledge management; Information behavior; Gestion des connaissances; Comportement dans la recherche de l'information.; SELF-HELP -- Personal Growth -- Memory Improvement; Knowledge management; Information behavior; Information behavior; Knowledge management; Informationsbeteende; Kunskapshantering